Trial Use of Inquiry Methods in Learning to Write Arabic in Junior High School Santi Asromo Majalengka - Ade Arip Ardiansyah (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Purpose - This study aims to test the ability of students when learning Arabic writing skills both after and before using survey methods. Design/methodology/approach - Because it aims to test effectiveness, researchers use quantitative-experimental methods with one group pre-test and post-test design. While the research object used as a sample is 8th-grade students at Santi Asromo Majalengka Middle School. Findings - The findings from the results of this study are, there are significant changes when learning to write using survey methods. With the details of t-count greater than t-table with an error level of 5% and the level of effectiveness is at the level of 53%. Originality/value – The implication of the results of this experiment is that teaching in the post method era does not mean eliminating a method in teaching. Furthermore, what will become a reflection for further research is how to position the method in the e-learning era and apply a method in it. Paper type – Research Paper